(untitled) (International Journal of Engineering and Computer Science, 2015)
:The purpose of this work is to develop a maximum power tracking control strategy forvariable speed wind turbine systems. Modern windturbine control systems are slow, and they depend on the design parameters of the turbine and use wind and / or rotor speed measurements as control variable inputs. The dependence on the accuracy of the measurement devices makes the controller less reliable. The proposed control scheme is based on the stiff system concept and provides a fastresponse and a dynamic solution to the complicated aero dynamic system. This control scheme provides a response to the wind changes with out the knowledge of wind speed and turbine parameters. The system consists of a permanent magnetsynchronous machine (PMSM), a passive rectifier, adc/dcboost converter, acurrent controlled voltages our ceinverter, and a micro controller that commands the dc/dcconverter to control the generator for maximum power extraction. The microcontroller will also be able to control the current output of the three-phaseinverter. In this work, the aerodynamic characteristics of wind turbines and the power conversion system topology are explained. The maximum power tracking control algorithm with avariable stepestimat or is introduced and the modeling and simulation of the wind turbine generator system using the MATLAB/SIMULINK® software is presented and its results show, at least in principle, that the maximum power tracking algorithm developed is suitable for wind turbine generation systems.